The microRNA-551a/MEF2C axis regulates the survival and sphere formation of cancer cells in response to 5-fluorouracil - Kang, Hoin; Kim, Chongtae; Ji, Eunbyul; Ahn, Sojin; Jung, Myeongwoo; Hong, Youlim; Kim, Wook; Lee, Eun Kyung (Molecules and Cells, 2019)
microRNAs regulate a diverse spectrum of cancer biology, including tumorigenesis, metastasis, stemness, and drug resistance. To investigate miRNA-mediated regulation of drug resistance, we characterized the resistant cell lines to 5-fluorouracil by inducing stable expression of miRNAs using lenti-miRNA library. Here, we demonstrate miR-551a as a novel factor regulating cell survival after 5-FU treatment. miR-551a-expressing cells (Hep3B-lenti-miR-551a) were resistant to 5-FU-induced cell death, and after 5-FU treatment, and showed significant increases in cell viability, cell survival, and sphere formation. It was further shown that myocyte-specific factor 2C is the direct target of miR-551a. Our results suggest that miR-551a plays a novel function in regulating 5-FU-induced cell death, and targeting miR-551a might be helpful to sensitize cells to anti-cancer drugs.
Keywords: Antimetabolites, Antineoplastic; Apoptosis; Base Sequence; Cell Survival; Down-Regulation; Drug Resistance, Neoplasm; Fluorouracil; Gene Expression Regulation, Neoplastic; Humans; MEF2 Transcription Factors; MicroRNAs; Spheroids, Cellular; Tumor Cells, Cultured; Anti-cancer drug resistance; Cell survival; Hepatocellular carcinoma; microRNA; Sphere formation